Human rights conflicts in Afghan 2004 constitution: shariah vs. international standards - Muhibullah Faizan,; Noor Shuhadawati Mohamad Amin,; Mohammad Tahir Sabit Haji Mohammad, (Penerbit Universiti Kebangsaan Malaysia, 2025)
In the discourse of human rights, tension emerged from the full involvement of the Western countries led by the United States of America “USA” in the 2004 constitution of Afghanistan “The 2004 Constitution”. It focuses on human rights under Shariah and international standards without unifying conflicting ideas after the Bonn Agreement of 2001. Hence, human rights are considered a subject of controversy among Afghan legal experts, law enforcement authorities and international community. It led to the lack of the rule of law due to constitutional duality. To fulfil the legal gap, this research seeks to discover the real position of human rights by evaluating the tension between legal provisions on Shariah and international human rights standards in the 2004 constitution. The research employs the doctrinal method of textual analysis and coordinated constitutional interpretation to discover the opposing areas of human rights under the Shariah and international standards. The researcher examined the legal status of human rights under constitutional provisions on Shariah and international human rights instruments which are introduced as conflicting sources of law for fundamental human rights, particularly about religious freedom and gender equality. Additionally, the 2004 constitution weakens the position of Shariah by restricting the meaning of law which does not contain the constitution itself, and by considering the provisions of international human rights instruments to be equated to the constitutional provision in ranking. However, the 2004 constitution prefers international human rights instruments to Shariah in the case of conflict either in legislation or in the judiciary.